Anti-inflammatory steroidal glycosides from the berries of Solanum nigrum L. (European black nightshade). (April 2018) - Xiang, Limin; Wang, Yihai; Yi, Xiaomin; He, Xiangjiu
Abstract: Seven previously undescribed steroidal glycosides, along with three known congeners were isolated from the unripe berries of Solanu m nigru m L. (Solanaceae). Their structures were elucidated on basis of 1D and 2D NMR, HR-ESI-MS spectroscopic data and GC analysis after acid hydrolysis. The potential inhibitory effects on nitric oxide (NO) production induced by lipopolysaccharide in RAW 264.7 cell line and the anti-proliferative activities against five cancer cell lines (HL-60, U-937, Jurkat, K562 and HepG2) were evaluated. Seven compounds exhibited inhibition activities on NO production with IC50 values ranging from 11.33 to 49.35 μ M. Structure-activity relationships of the isolated compounds were also discussed. Graphical abstract: Seven previously undescribed steroidal glycosides along with three known congeners were isolated from S. nigru m L. Several of them showed potential anti-inflammatory activity in vitro . Highlights: Seven previously undescribed steroidal glycosides were isolated from Solanum nigrum . Structures were elucidated through IR, 1D, 2D NMR and HR-ESI-MS. Some steroidal glycosides exhibited potent anti-inflammatory and antiproliferative activities.